2012
DOI: 10.1002/mbo3.45
|View full text |Cite
|
Sign up to set email alerts
|

The differential susceptibility of spores from virulent and attenuated Bacillus anthracis strains to aldehyde‐ and hypochlorite‐based disinfectants

Abstract: This study compared the sensitivity of spores from virulent and attenuated Bacillus anthracis strains in suspension to inactivation by various chemical disinfectants. Spore suspensions from two virulent strains (A0256 and A0372) and two attenuated strains (Sterne and A0141) of B. anthracis were tested against two aldehyde-based disinfectants and one hypochlorite-based disinfectant. A novel statistical model was used to estimate 4-log10 reduction times for each disinfectant/strain combination. Reduction times w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This was also noted with the virulent Ames strain; although this strain was more resistant to both decontaminants especially sodium hypochlorite at five minutes of contact time. This difference in susceptibility to decontamination between the two strains has been noted previously [ 31 33 ]. Other studies have shown that the differences between strains are minor and dependent on the type of disinfectant used [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 80%
“…This was also noted with the virulent Ames strain; although this strain was more resistant to both decontaminants especially sodium hypochlorite at five minutes of contact time. This difference in susceptibility to decontamination between the two strains has been noted previously [ 31 33 ]. Other studies have shown that the differences between strains are minor and dependent on the type of disinfectant used [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 80%
“…A comparison of the 6-log 10 reduction time values for selected Bacillus spores confirms that not all spores share the same sensitivity to GTA (March et al, 2012). Mild variations existed in kill times between different batches of identical spore species, but these were not statistically significant.…”
Section: Discussionmentioning
confidence: 82%
“…Proper understanding, use, and development of disinfectants are an essential aspect of decreasing the costs and complications associated with modern health care and curbing the spread and development of resistant microbes that pose an increasingly problematic threat to public health. Bacterial endospores have received particular attention due to their notorious stability, resistance to chemical germicides, and their clinical significance (Christensen et al, 1989; March et al, 2012). Because of this, sporicidal activity is an important aspect of liquid sterilization claims, and disinfection research generally.…”
Section: Introductionmentioning
confidence: 99%
“…The biocidal activity of the gel thus involves two steps spore absorption-spore inactivation. First, the Bt spores are adsorbed into the gel and, as the gel dries, the known biocidal activity of the hypochlorite ions [1,13,15] ensures that the Bt spores are neutralized. This mechanism is consistent with the fact that the NaOH-gel is ineffective 20 against Bt spores, with a log reduction in CFU of less than 1.1 obtained with a fresh sample (Fig.…”
Section: Gel Efficiency Against Biological Agents and Associated Deco...mentioning
confidence: 99%
“…Currently available CBRN decontamination technologies include physical, chemical and biological processes [4,8,9]. Chemical decontamination products often contain an oxidant such as peroxides or hypochlorite ions [8][9][10], which are effective against biological and chemical contaminations [11,12], with hypochlorite also being particularly effective against a large variety of spores and microorganisms [1,[13][14][15]. Against chemical agents, while a basic medium effectively hydrolyzes (and thus neutralizes) sulfur mustard and nerve agents such as soman [11,16,17], an oxidant is required to neutralize other nerve agents such as VX.…”
Section: Introductionmentioning
confidence: 99%